Reliable identification of the complex or superlattice nature of intrinsic and extrinsic stacking faults in the L12 phase by high-resolution imaging - Karpstein, Nicolas; Lenz, Malte; Bezold, Alexander; Wu, Mingjian; Neumeier, Steffen; Spiecker, Erdmann (Acta Materialia, 2023)
Planar defect-based deformation mechanisms are becoming increasingly important for understanding and tuning the mechanical properties of superalloys. Typically, to elucidate such deformation mechanisms, the type of planar defect is determined by conventional transmission electron microscopy or by high-resolution imaging along 〈110〉 crystallographic directions. However, an unambiguous identification of the complex or non-complex nature of intrinsic and extrinsic stacking faults in the L12 phase may not be possible by analyzing only one projection. To overcome this limitation, we present a straightforward approach to identify the superlattice or complex character of intrinsic and extrinsic faults in the L12 structure in high-resolution scanning transmission electron microscopy by tilting to a different zone axis and examining the shift of superlattice planes. Using this approach, two key aspects of the Kolbe mechanism for the formation of superlattice extrinsic stacking faults are verified for the first time: the presence of a complex intrinsic fault segment at the leading end and the occurrence of re-ordering.
CRIS-Team Scopus Importer:2023-09-22
Keywords: Creep; Dislocation; Electron microscopy; Planar defects; Superalloy